El programa “Regla y compás”. Una experiencia utilizando un software gratuito para generar ambientes de aprendizaje en matemática - Zuleyka Suárez Valdes-Ayala; Paulo García-Delgado (Revista Electrónica Educare)
The program “Regla y Compás” (“Ruler and Compasses”) is useful to support the teaching of Math processes in geometry by means of a computer. One of the advantages it offers is that it may be obtained gratuitously in the internet. The way in which this type of programs allows for corporative and interdisciplinary work will by analyzed. For this purpose, the experiences obtained during the research project “Teaching high school mathematics whit free online software: The Ruler and Compasses case” will be discussed. The latter enabled the elaboration of tree manuals: “User's manual”, “Student's manual” and Teacher`s manual”. The objective is to facilitate the teaching of geometry through 32 practice and learning sessions.